The Cellular and Synaptic Location of Activated TrkB in Mouse Hippocampus During Limbic Epileptogenesis - Helgager, Jeffrey (2013)
Understanding the mechanisms of limbic epileptogenesis in cellular and molecular terms may provide novel therapeutic targets for its prevention. The neurotrophin receptor, tropomyosin-related kinase B (TrkB), is thought to be critical for limbic epileptogenesis. Enhanced activation of TrkB, revealed by immunodetection of enhanced phosphorylated TrkB (pTrkB), a surrogate measure of its activation, has been identified within hippocampus in multiple animal models. Knowledge of the cellular locale of activated TrkB is necessary to elucidate its functional consequences. Using an antibody selective to pTrkB in conjunction with confocal microscopy and cellular markers, we determined the cellular and subcellular locale of enhanced pTrkB induced by status epilepticus (SE) evoked by infusion of kainic acid into the amygdala of adult mice. SE induced enhanced pTrkB immunoreactivity in two distinct populations of principal neurons within hippocampus, the dentate granule cells and CA1 pyramidal cells. Enhanced immunoreactivity within granule cells was found within mossy fiber axons and giant synaptic boutons. By contrast, enhanced immunoreactivity was found within apical dendritic shafts and spines of CA1 pyramidal cells. A common feature of this enhanced pTrkB at these cellular locales is its localization to excitatory synapses between excitatory neurons, presynaptically in the granule cells and postsynaptically in CA1 pyramidal cells. Long term potentiation (LTP) is one cellular consequence of TrkB activation at these excitatory synapses that may promote epileptogenesis.